Culinary Tourism Attractions In The Tugulufa Area In Supporting The Tourism Industry In The City Of Tidore Islands - Yudian, Rais A; Demolingo, Ramang Husin (Jurnal Manajemen Pelayanan Hotel, 2022)
One area that has a promising culinary tourism attraction is the City of the Tidore Islands, precisely in the Tugulufa area. The purpose of this study is to discuss the attraction of culinary tourism in the Tugulufa area, its potential, and how culinary tourism supports the tourism industry in the Tidore City. The method used is descriptive analysis and matrix analysis of internal factor evaluation and external factor evaluation. The result is a tourist attraction and potential in the form of a comfortable place, a variety of culinary menus, low prices, distinctive culinary delights, and close to the beach, making culinary tourism able to support the tourism industry in the City of Tidore, Islands. Keywords: Tourist attractions, culinary tours, Tugulufa area, tourism industry